Pengaruh Tekanan Klien Dan Rotasi Audit Terhadap Independensi Auditor: Pendekatan Eksperimen - Prima Rosita Arini; Fachmi Yandra (Owner : Riset dan Jurnal Akuntansi, 2022)
The auditor is an external party who will check and ensure that the client's financial statements are free from material misstatement so that the quality of the audit provided must be good. Therefore it is important for an auditor to have an independent attitude. Independence is a basic attitude that must be possessed by an auditor because the auditor is required to be impartial to one party. But in reality, to maintain independence is not easy. One of the factors that affect the independence of an auditor is client pressure. In previous studies, it was found that client pressure was able to affect auditor independence because the pressure was related to audit fees. With the pressure there is a possibility of decreasing the level of auditor independence. In order to maintain independence, an effort is needed, one of which is auditor rotation. Auditor rotation is auditor rotation that must be carried out by the company, with the aim of producing good audit quality and maintaining auditor independence. Auditor rotation is also carried out to prevent a close relationship between the auditor and his client. Based on these circumstances, this study was conducted to examine the effect of audit rotation and client pressure on independence. Data collection was carried out through the 2 X 2 experimental method between subjects. The participants in this research experiment were students, lecturers/teachers, auditors and other occupations. The experiment was carried out using the help of information technology. The experimental task given is an adjustment audit. The results showed that client pressure had an effect on auditor independence and auditor rotation was able to increase auditor independence. However, the results of this study have not been able to prove interaction hypothesis between client pressure and auditor rotation on auditor independence.